Necrolytic Acral Erythema in a Seronegative Patient: A Rare Presentation of a Rare Dermatosis - Neha Mariam Joseph; Thillaikkarasi A; Narasimhalu CRV; Sridevi M (Dr. Annil Mahajan, 2023)
We report a 34-year-old man who presented to us with mildly pruritic bilaterally symmetrical brownish plaques over the dorsum of both hands and feet for 2 months, whose dermatological and histopathological findings were in accordance with necrolytic acral erythema, but the serologic marker for hepatitis C virus was negative. He showed irrefutable clinical improvement with oral zinc therapy. Very few cases of necrolytic acral erythema without the presence of HCV infection has been reported, which led to this report.